Social Media Marketing and Product Quality on Purchase Intention of All-You-Can-Eat Restaurant - Surianto, Surianto; Yulita, Henilia; Wijaya, Brendi; Ibrahim, Audi Arief (Jurnal E-Bis, 2024)
Social media marketing is a technique for someone to carry out marketing activities through social media or word of mouth, by promoting products to potential consumers in online platform. Pempek-Yuk Restaurant! is the first restaurant to provide culinary with the "All-you-can-eat" concept. This research aims to see whether interest in buying all-you-can-eat, is influenced by social media marketing and the quality of Pempek-Yuk! The research method was quantitative, using SPSS25 analysis tool and purposive sampling with Likert scale. The population was the millennial who live in Jakarta with total sample of 192 respondents. It is concluded that the buying interest of the millennial generation is influenced by social media marketing positively and significantly. The purchasing interest of the millennial generation is influenced by product quality positively and significantly. This study also shows that people's buying interest is influenced by social media marketing and product quality simultaneously, positively and significantly.